Gas permeability properties of decorated MCM-41/polyethylene hybrids prepared by in-situ polymerization - Bento, A. (2013)
Mixed matrix membranes, MMM, based on polyethylene,PE, and silica mesoporous material, MCM-41, have been prepared using these hybrid materials obtained by in situ polymerization in order to achieve higher permeability, selectivity or both magnitudes relative to the existing polymeric PE membranes. Different methodologies are used to enhance interfacial adhesion between components, PE matrix and MCM-41. These basically consist of promoting the modification of MCM-41 surface with undecenoic acid, UA/triisobutylaluminum, TIBA, system before the polymerization and of incorporating UA in the polymer chains by copolymerization. The influence of UA on the degradation behavior is evaluated for all of the hybrids and the transport properties, in terms of permeability and diffusivity coefficients as well as permselectivity at different gases and temperatures are checked in some of the resulting materials.